The three billy goats gruff: read it yourself with ladybird level 1 - Percy, Graham (Ladybird London, 2006)
Over the years, the classic Ladybird fairytale has delighted children and adults alike. Featuring artwork and retellings, this book and CD pack helps children with word recognition.